2001
DOI: 10.1101/gr.184501
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Classification of Differentially Expressed Genes in Renal Cell Carcinoma by Expression Profiling on a Global Human 31,500-Element cDNA Array

Abstract: We investigated the changes in gene expression accompanying the development and progression of kidney cancer by use of 31,500-element complementary DNA arrays. We measured expression profiles for paired neoplastic and noncancerous renal epithelium samples from 37 individuals. Using an experimental design optimized for factoring out technological and biological noise, and an adapted statistical test, we found 1738 differentially expressed cDNAs with an expected number of six false positives. Functional annotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
2
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(150 citation statements)
references
References 43 publications
(41 reference statements)
13
133
2
1
Order By: Relevance
“…Parvalbumin is a calcium-binding protein proposed recently as a useful marker to identify renal epithelial neoplasms with differentiation toward the distal nephron such as chromophobe renal cell carcinoma and oncocytoma. [13][14][15] In this study, we demonstrated that parvalbumin immunostained all 42 chromophobe renal cell carcinoma and used Western blot analysis to Endogenous biotin in kidney tissue and renal tumors can lead to confusing results. In this study, three different developing systems that are not sensitive to endogenous biotin were used to overcome this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Parvalbumin is a calcium-binding protein proposed recently as a useful marker to identify renal epithelial neoplasms with differentiation toward the distal nephron such as chromophobe renal cell carcinoma and oncocytoma. [13][14][15] In this study, we demonstrated that parvalbumin immunostained all 42 chromophobe renal cell carcinoma and used Western blot analysis to Endogenous biotin in kidney tissue and renal tumors can lead to confusing results. In this study, three different developing systems that are not sensitive to endogenous biotin were used to overcome this problem.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 So far, most microarray studies on RCC metastasis comprise metastatic and nonmetastatic primary RCC. 9,10 Only a few studies include Mets of RCC to identify expression patterns associated with metastatic spread [11][12][13] since fresh-frozen metastatic lesions are rare because of their restricted surgical treatment. However, these studies have never addressed the particular characteristics of metastatic spread mentioned above.…”
mentioning
confidence: 99%
“…MUC18 and VCAM-1 adhesion molecules, LOX-1, laminin and collagen IV) are also overexpressed, suggesting that this feature may be involved in the progression of RCC. 2,27 The overexpression of several interferon-regulated genes (IIP-9-27, IFI-27, GBP2, MIG, IFI-16 and TAP-1) may explain the clinical benefit of IFN therapy in RCC.…”
Section: Studies On Genetic or Protein Profilesmentioning
confidence: 99%
“…A further development in the field may come from the data obtained from global genomic studies revealing gene signature of clear cell RCC containing several IFN-responsive genes. 2,27 The determination of the expression of IFN-responsive genes in the individual RCC, and analysis of the success of cytokine therapy may identify novel predictive markers for this type of therapy.…”
Section: Targeting Genes and Pathwaysmentioning
confidence: 99%